2018
DOI: 10.1016/j.foodchem.2017.07.090
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccessibility of Ca, Cu, Fe, Mg, Zn, and crude protein in beef, pork and chicken after thermal processing

Abstract: The bioaccessibility of Ca, Cu, Fe, Mg, Zn, and crude protein was evaluated after submitting beef, pork, and chicken to five different thermal treatments. The bioaccessibility of crude protein and metals were simulated by using in vitro enzymatic digestion with a gastric fluid solution and dialysability approach. Inductively coupled plasma optical spectrometry was used to quantify the dialyzable fraction and the total mineral content after microwave-assisted digestion. Graphite furnace atomic absorption spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 30 publications
1
30
3
Order By: Relevance
“…Menezes, Oliveira, Franca, Souza, and Nogueira () showed that the values of Ca (105 mg/kg), Cu (1.9 mg/kg), Fe (49 mg/kg), Mg (763 mg/kg), and Zn (172 mg/kg) in raw beef are higher than in the analyzed samples, except for the level of Ca in MLT muscle of bulls from kosher slaughter, the value of which was 11.70 mg/100 g. The contents of Ca determined by Gerber et al (Gerber, Scheeder, & Wnek, ) in beef elements (5.4–7.0 mg/100 g) are at a similar level as in the author's own research.…”
Section: Discussionmentioning
confidence: 97%
“…Menezes, Oliveira, Franca, Souza, and Nogueira () showed that the values of Ca (105 mg/kg), Cu (1.9 mg/kg), Fe (49 mg/kg), Mg (763 mg/kg), and Zn (172 mg/kg) in raw beef are higher than in the analyzed samples, except for the level of Ca in MLT muscle of bulls from kosher slaughter, the value of which was 11.70 mg/100 g. The contents of Ca determined by Gerber et al (Gerber, Scheeder, & Wnek, ) in beef elements (5.4–7.0 mg/100 g) are at a similar level as in the author's own research.…”
Section: Discussionmentioning
confidence: 97%
“…Bioaccessibility of different metals has been estimated so far in breads [4], fruits and vegetables [4][5][6][7], fruit juices [8,9], coffees [10][11][12], milks [13,14], herbal remedies [15], infant formulas [13,16], meat [17], linseed, sesame and cereals [16,18], and edible seaweeds [19][20][21]. Unfortunately, just few papers were devoted so far to bioavailability/bioaccessibility of selected metals from tea infusions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, in vitro gastrointestinal digestion has been applied to estimate bioaccessibility of elements from various food products and beverages, including fruit juices (Cautela et al 2009;de Lima et al 2014;Haro-Vicente et al 2006), infant formulas (Bermejo et al 2002;do Nascimento da Silva et al 2017), tea (Powell et al 1998;Erdemir 2018), herbal infusions (Pereira Junior et al 2018;Zhou et al 2014), GCs and ICs (Stelmach et al 2014(Stelmach et al , 2016, slim coffees (Szymczycha-Madeja et al 2015), chocolate drink powder (Peixoto et al 2013), various milks (Bermejo et al 2002;Chaiwanon et al 2000;Shen et al 1995), honey (Pohl et al 2012), fruits and vegetables (do Nascimento da Silva et al 2015;Khouzam et al 2011;Machado et al 2017;Oliveira et al 2018;Pereira et al 2016), breads (Gawlik-Dziki et al 2009;Khouzam et al 2011;Lamsal and Beauchemin 2015), cereals (do Nascimento da Silva et al 2017), white cheeses (Khouzam et al 2011), various meats (Menezes et al 2018), and edible seaweeds (Dominguez-Gonzalez et al 2010;García-Sartal et al 2011. Commonly, a two-step procedure that simulates stomach and intestinal digestion with solutions of pepsin in the gastric phase and a mixture of pancreatin and bile salts in the intestinal phase is used.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, elements released to soluble or dialyzable fractions are determined by flame atomic absorption spectrometry (F AAS), inductively coupled plasma optical emission spectrometry (ICP OES), and inductively coupled plasma mass spectrometry (ICP-MS). Before spectrochemical analysis, resulting sample solutions can be initially prepared with the aid of open-vessel or closedvessel wet digestions (do Nascimento da Silva et al 2015;García-Sartal et al 2011Peixoto et al 2013; or analyzed directly, i.e., without any pre-treatment (de Lima et al 2014;Dominguez-Gonzalez et al 2010;do Nascimento da Silva et al 2017;Erdemir 2018;Khouzam et al 2011;Lamsal and Beauchemin 2015;Menezes et al 2018;Pereira et al 2016;Pereira Junior et al 2018).…”
Section: Introductionmentioning
confidence: 99%